How can the transition from office to telework be managed? The impact of tasks and workplace suitability on collaboration and work performance - Müller, Tobias; Schuberth, Florian; Bergsiek, Micha; Henseler, Jörg (Frontiers in Psychology, 2022)
As COVID-19 has brought to surface the need for workplace digital transformation due to a rapid transition from office to remote work, employers must make telework suitable for original office workers who suddenly became permanent telecommuters. By using partial least squares path modeling, this article suggests the defining of telework tasks suitability and of telework workplace suitability by performing an empirical study with 691 employees who experienced a rapid transition from office work to remote work during the pandemic. Both telework tasks suitability and telework workplace suitability have a positive relationship with collaboration and work performance. Employers should especially focus on communication technology when making employees work from home to foster work performance and enable collaboration to prevent them from feeling isolated. This study is the first to define telework tasks suitability and workplace suitability to enable collaboration and to increase work performance of teleworkers after an enforced transition from office to telework.